Effects of fresh-cow diseases on reproduction in a large commercial dairy herd - Tollefsrud, Ryan Peder (Kansas State University, 2012)
The 2007 NAHMS (National Animal Health Monitoring System) survey indicated that early lactation health issues are major factors influencing reproduction and culling on U.S. dairy herds. The objective of this study was to evaluate fresh-cow health during the first 30 days in milk, and its association with days to pregnancy in the concurrent lactation. Data were collected on cattle that calved over a two month period (July and August 2009) on a dairy farm located in the Upper Midwest region of the U.S. Health and production data were collected daily for each cow from the beginning of lactation until the majority of the study population was confirmed pregnant. Both a competing risk analysis and a semi-parametric Cox regression model were used to test the association between specific health-related events and days to pregnancy and the outcomes of the two models were compared. These analyses showed metritis and dystocia in the first 30 days of lactation were associated with greater days to pregnancy. The only difference noted between parities was that lactation-five and greater cows were significantly associated with greater days to pregnancy. The two analyses showed conflicting significance of association between retained placenta, ketosis, twinning, lameness, and other non-specific illnesses with days to pregnancy. This study found that a competing risk analysis and a semi-parametric regression model were appropriate methods to analyze time sensitive data such as reproductive efficiency. This study supports the evidence that parity, metritis, retained placenta, ketosis, dystocia, twinning, lameness, and other non-specific illnesses can have an impact on reproductive efficiency.
Keywords: Dairy cattle; Reproduction; Postpartum disease; Competing risk; Agriculture, General (0473)